Fortalecimiento del Vínculo Escuela-Familia desde el Enfoque del Autodesarrollo Comunitario en el Proceso de Enseñanza-Aprendizaje del Quinto Año de Educación Básica, Escuela Bogotá de la Parroquia Orianga, Cantón Paltas, Provincia de Loja, 2014 - Jumbo Cuenca, Matilde Genoveva (2016)
This research work was developed to analyze the strengthening of the family link school, from the standpoint of community self in the educational process of teaching and learning in the fifth year of basic education in Bogota Orianga Parish School Region Paltas province of Loja who had requested for community strengthening that enhances and reinforces the school family link to the different educational institutions doing some work in his parish. The Bogota School, has no academic training of teachers, it maintains a low level of psychological and emotional relationship between parents and teachers. They have an outdated methodology that leads to a good logical and creative thinking. This reality obliges minutely investigate, find elements that allow for intervention from the perspective of community self in the fifth year of basic education in this institution. A research was built it with the commitment of the authorities of the institution ateachers, staff and parents of the Bogotá School Orianga Parish, adjusting into five workshops, through a reflection of the problem, the analysis of how to contribute to its strengthening. The meetings and the work was formalized with workshops assisted with group dynamics and exchange materials; they reflected forward from what has been done by the institution and development on the commitments made by the entities surveyed, the main contribution of this research would be achieved, generate a program of community self to build a strengthening process that allows enhance and assess the active participation of teachers and parents-mothers of the Bogotá School Orianga Paltas Canton parish in the province of Loja. The school, family and community are the contexts in which humans develop and learn, so they must exist between integration and responsibility in the educational process, in this sense, the research was aimed at providing participatory strategies aimed at teachers, parents and representatives in order to strengthen the integration school - family and community in the process of teaching and learning. This study allowed us to establish that teachers do not apply to families strategies to invigorate the joint work and the representatives expressed receive no guidance on the education of their children. It is 5 recommended to promote integration between school - family and community, to strengthen the comprehensive development of children, through the process of teaching and learning. In the working sessions it took an important place theme, initially attendees were apathetic to the proposed construction of the intervention project aimed at strengthening the link between school and family of the fifth year of primary school teaching Bogota, Parish Orianga, Paltas Cantón, but then became involved with the intervention of the professional in the field. The applicants themselves recognize that strengthening school-family relationships network enables better development processes of individual, family, institutional and community. Through the methodology of Community Self, was achieved that managers, teachers, and parents where he was directed the survey and interview have a critical awareness of the need to break with the traditional management and adopt instead a educational management that encourages the role of the actors through the participation and cooperation in projects of School-Family link. The objective of this research to develop a project to strengthen the school-family Bogota fifth year of school, link it to contribute to the active participation of children was achieved. In addition, demand was evident attendees in the working sessions that were conducted in the institution itself. The intervention process carried out at this institution, helped to promote principles of solidarity, work and participatory development as human development is an entity that is always looking for the best, so cultivating habits of social coexistence, democracy and wholesome association. This is a project that is being implemented and strengthened.